Análise espacial da microcefalia associada ao vírus Zikaem Fortaleza–Ceará - Santos, Daisyanne Augusto de Sales (2019)
Microcephaly is a rare condition that had an increased number of cases since 2015 and it is reportedly associated with Zika Virus infection during pregnancy. This study aims to analyze the spatial distribution of cases of microcephaly associated with Zika Virus in Fortaleza, Ceará, Brazil. This is an ecological study focusing on spatial analysis conducted in the city of Fortaleza from 2015 to 2017. The data sources were the following Information Systems: Event Management System, Live Birth Information System, The Mortality Medical Data System, Information System for Notifiable Diseases and Disease Surveillance System. Social Data by neighborhoods were captured from the Demographic Census from 2010. The data were collected and analyzed from September 2018 to January 2019. The locations were georeferenced with the cartographic base concerning 121 neighborhoods in Fortaleza. Epidemiological characteristics were analyzed using descriptive statistics. To identify the spatial pattern, data from the areas were analyzed by the Global and Local Moran Index, and by the mapping techniques BoxMap, LISAMap and MoranMap. We used the Terraview 5.4, GeoDa and QGIS 2.14 to obtain the calculations about spatial autocorrelation, significance tests and graphic illustrations. From 2015 to 2016 there was an outbreak of microcephaly caused by the introduction of the Zika Virus in Fortaleza, with 53 cases of microcephaly confirmed associated with congenital infection by Zika Virus and no cases in 2017. We observed that 58.5% of these children are males, with full term births and adequate Apgar scores and weight for their age. In addition, 47.2% were diagnosed in the intrauterine period and 22.6% of the cases evolved to death. In the descriptive analysis, most women were in the 24-year age group, attended high school, were single and unemployed in the moment of childbirth. Regarding prenatal and delivery aspects, most women attended an average of seven consultations, starting at the first trimester of gestation and had a cesarean delivery in public network hospitals. In spatial analysis, common areas with high incidence rates of Zika and microcephaly were identified. Moran's I value demonstrated the presence of clusters (positive auto spatial correlation) in which neighborhoods with high rates of Zika microcephaly are neighbors to others with the same characteristic, presenting neighborhoods with a higher level of significance of p < 0.05 in 2015 and p < 0.01 in 2016. Most of these cases are within or near areas of precarious settlements, with high risks for arboviruses epidemic and low Human Development Index. From this spatial analysis it was possible to identify the concentration areas of microcephaly by Zika. The cases did not occur randomly and are related to the socioeconomic scenario, suffering influence from living conditions and infection rates in neighboring areas. It was possible, with this information, to identify the need to invest in public policies and actions for health promotion and surveillance, improving the monitoring of the growth and development of children with Microcephaly.